Kajian Yuridis Pelaksanaan Roya Obyek Hak Tanggungan Atas Tanah Oleh Badan Pertanahan Kota Mataram - Wiwiek Wahyuningsih; Arba -; Shinta Andriyani (Fakultas Hukum Universitas Mataram, 2018)
Deposit Rights is the right to pledge the right to land as a credit guarantee to the Bank. The Deposit Rights is an accecoire agreement (agreement) of the main agreement, namely debt agreement receivable. The right of Dependent must be made a Deed of Granting of Dependent Rights and must be registered in the Land Registry Office of the National Land Agency to obtain a certificate for guarantee of legal certainty, and must also diroya 'if the debts are due. Roya is a deletion of the security expense of a land right that is the object of the Mortgage Right that has expired or has been removed because it has already ended its credit by the Land Registry Office at the request of the interested parties. This research is empirical law research that aims to examine the juridical-empirical implementation of roya Object of Mortgage by the Land Registry Office of Mataram City. The result of the research shows that the implementation of registration of the Land Rights of the Land on Land has been clearly regulated with the requirements and procedures. While the implementation of Roya Object of Mortgage Rights at the Office of BPN Kota Mataran has been implemented well in accordance with the provisions and procedures that have been determined by the applicable legislation.